The case of the diagnosis of left atrial myxoma, first manifestation of which was in the acute ischemic stroke - R. M. Vitovsky; V. V. Isaenko; A. A. Pischurin; I. V. Martyshchenko; D. N. Dyadyun (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article demonstrates an unusual case of diagnosis of myxoma of the left atrium (LA) on the background of an acute cerebrovascular accident (ACVA), which took place at the city hospital in Lutsk, after which the patient was sent to the N. M. Amosov National Institute of Cardio-Vascular surgery of the Academy of Medical Sciences of Ukraine. According to emergency indications removed aciniform myxoma LA with multiple fragments, the tear of which could cause re-embolism of vessels of the systemic circulation.